กรอบแนวคิดของแผนแบบการสุ่มตัวอย่างแบบกลุ่มปรับ - วิชาญ โชควิวัฒน (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The objective of this study is to study of conceptual Adaptive Cluster Sampling and concept of simple random sampling without replacement under Adaptive Cluster Sampling by Steven K. Thompson (1990) for mean estimators which have been modified from the Horvitz-Thompson. The thesis also presents the comparison of the efficiency for mean estimators under an initial simple random sampling without replacement under Adaptive Cluster Sampling and Nonadaptive by Relative Efficiency : R.E. In order to make the comparison, the studied areas have been divided into 100 units. The populations are simulated by poisson cluster process with parameter λ = 20. Simulatation of populations in 3 cases and surrounded by Bivariate Normal with sample size of 4,8,16 and 32 units. Each sample size is divided into 100 models. The result shows that in comparison of the efficiency in term of accuracy for mean estimators of initial simple random sampling without replacement under Adaptive Cluster Sampling and Nonadaptive illustrates that mean estimators under Adaptive Cluster Sampling is more efficient than mean estimators under Nonadaptive in all 3 cases and in every sample size, including n= 4, 8, 16 and 32. By increasing in sample size will result in more accuracy in both methods. And Adaptive Cluster Sampling is suitable for random sampling of interested properties which are in single cluster. This could be the category of scarce properties, for instance, herd of cattle, various kind of plants, fossils and mineral resources. For Nonadaptive is suitable for interested properties which are dispersed.